Modelling and analysis of IEC 61850 for end-to-end delay characteristics with various packet sizes in modern power substation systems - Wong, T.; Das, Narottam (2014)
Substation is an important part of electricity generation, transmission and distribution system, where voltage is stepped up and down or vice versa. The substation serves as a centre point of all kind of connection between various power systems, such as the distribution line from electricity generation plant to the household or industrial consumers. There are different types of substation, such as transmission, distribution, collector, switching substations, and so on. In these substations, there are several common power system equipment's that involves the transformation process of electrical power through the circuit breakers, power transformers, protection relays, and associated equipment's. Hence, the end-to-end delay characteristic in substation communication system is much concern in order to ensure high reliability and availability of the substation function capability. In this paper, we model, simulate and compare the end-to-end delay characteristics among different data packet sizes as well as different types of substation network topologies using IEC 61850. The simulation results confirm that the larger packet sizes have higher amount of delays compare to the smaller packet sizes. Besides that, communication network topology with higher amount of IEDs will result in a higher end-to-end delay. Therefore, based on the obtained results, it is recommended to reduce the end-toend delay of substation communication data flow for sustainable and reliable modern power systems.